The Role of Development Communication in Leadership and Innovation in Independent Village Development - Muhammad Luthfie Supandi; Mohd Nor Shahizan Ali; Rohani Pooteh; Zurinah Tahir; Pandji Santosa (Jurnal Mamangan, 2026)
This article discusses village development issues, which are part of the village management program. The focus of the problem is the role of development communication in the village government's process of achieving the Independent Village title, which is the goal of all village governments as a measure of the success of the development process. Gunung Putri Village has achieved this title and is currently the target of a comparative study with several other villages. Based on preliminary studies, the success of Gunung Putri Village is due to the intensification of development communication, which has produced strong leadership and innovation within it. The purpose of this study is to analyze the role of development communication in developing leadership and innovation in the effort to achieve the Independent Village. The research theory used is the development communication theory, developed by academics from IPB University. The study used a qualitative approach. Data collection was carried out through observation, in-depth interviews, focus group discussions, and document analysis. The study presents findings on the role of development communication in strengthening leadership, encouraging innovation, and formulating an independent village model. The development of leadership and innovation by the village government and other stakeholders is the driving force behind Gunung Putri Village's success in achieving the independent village title. This is closely related to the effectiveness of development communication. The conclusion of this study states that the role of development communication in strengthening leadership and community participation in innovation development is a crucial factor in achieving independent villages. The research process has identified a model for the development of self-sufficient villages, which is also a novelty in the research underlying this article. This model differs from other models in village development, as it is recommended for building self-sufficient villages.